Implementation of Islamic Education Management in the Development of Digital Madrasahs: A Case Study at MIS Terpadu Kota Langsa - Zulfahji Zulfahji; Mesiono Mesiono; Muhammad Dalimunte (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2026)
Digital transformation in madrasah ibtidaiyah presents challenges in integrating technology into learning processes grounded in Islamic educational values. This study aims to analyze the implementation of Islamic education management in the development of digital madrasahs and to explore the use of technology in supporting learning, assessment, and students’ digital literacy at MIS Terpadu Kota Langsa. The study employs a qualitative approach with a case study design, involving the principal, teachers, and educational staff as informants through in-depth interviews, observations, and documentation. Data were analyzed using a descriptive-analytical approach with source triangulation and member checking to ensure data validity. The findings indicate that digital classes are implemented for students in grades 4–6 through a readiness-based and contextual approach, taking into account cognitive readiness, foundational literacy, and parental support. Learning Management Systems (LMS) and digital learning applications strengthen the management of learning materials and activities, while digital-based final examinations function as tools for both assessment and the development of technological literacy. Digital transformation also enhances teachers’ professional roles and highlights the importance of integrating Islamic values into decision-making processes. This study emphasizes that the success of digital madrasahs is determined by the institution’s ability to manage technology in an ethical, pedagogical, and contextual manner. Theoretically, this study contributes new insights into the principles of Islamic education management that support the development of digital madrasahs, ensuring that technological transformation in primary education remains aligned with the values of tarbiyah. Keyword: Digital Madrasah, Islamic Education Management, Primary Education